1913 Iowa Acts 307 - (:unkn) unknown (My University, 1913)
Ch. 297, §§ 1, 2: Prohibited the carrying of a concealed dirk, dagger, sword, pistol, revolver, stiletto, metallic knuckles, picket billy, sandbag, skull cracker, slungshot, or other offensive and dangerous weapons or instruments. Also prohibited the selling, keeping for sale, offering for sale, loaning, or giving away any dirk, dagger, stiletto, metallic knuckles, sandbag, or "skull cracker." Exempted the selling or keeping for sale of "hunting and fishing knives."
Keywords: CARRY - CONCEALED; TRANSFER - NON-GUN ARMS